A FATAL RUPTURE OF A CEREBRAL ANEURYSM IN A ROAD TRAFFIC ACCIDENT: TRAUMATIC OR SPONTANEOUS! (Journal of Forensic Medicine & Toxicology, 2024)
An aneurysm is an abnormal dilatation or bulging in a blood vessel due to the intrinsic weakness of the vessel wall. Cerebral aneurysms are more common over the age of 40, with a female-to-male ratio of 2:1. We report a case of a 56-year-old female rear passenger of a motorised two-wheeler with an alleged history of dizziness and fall from the bike. Following this, she had altered sensorium and loss of consciousness and presented to the casualty with a Glasgow coma scale (GCS) score of 10. On examination, the left pupil was not reacting to light; left eye proptosis and drooping of the eyelid were present. Radiological investigations diagnosed it as a left posterior communicating artery (PCOM) ruptured saccular aneurysm. Clipping of the left posterior communicating artery aneurysm was done. Later, the patient’s health deteriorated, and she died. On autopsy, diffuse subarachnoid haemorrhages were present over the basal region, and bilateral intraventricular haemorrhage was present. The base of the brain showed aneurysmal clipping at the PCOM artery. In this case report, we discuss the challenging aspects of finding the  relationship between trauma and rupture of cerebral aneurysm.
Keywords: Aneurysm; Forensic pathology; Posterior communicating artery; Road traffic accident; Rupture; Subarachnoid haemorrhage